The effect of perceived value by the tourists toward electronic word of mouth activity: the moderating role of conspicuous tendency - Sukaris Sukaris; Sri Hartini; Dien Mardhiyah (Jurnal Siasat Bisnis, 2020)
Managers of tourist destinations are currently trying to offer attractions and attractive destination resources to be visited by tourists. However, very few managers of tourist destinations, especially adventure tourism who pay attention to the values that will be obtained by tourists and also very little attention to the tendency behavior of consumers to show off when visiting tourist attractions, in which they will then recommend their activities to others through digital media. The purpose of this study is to analyze the effects of the perceived values by tourists, consisting of emotional value and epistemic value towards the activity of electronic word of mouth of tourists moderated by conspicuous tendencies. The population in this study is visitors who carry out adventurous activities in adventure tourism destinations, with a sample of 400 tourist. Hypotheses are tested by using structural equation modeling. The results of the study provide information that the emotional value affects the activity of electronic word of mouth of tourists. Likewise, the novelty value influences the activity of electronic word of mouth of tourists, while the conspicuous tendencies variable of tourists weakens the effect of emotional value on the activity of electronic word of mouth of tourists. Finally, the conspicuous tendencies variable of tourists can be a variable which strengthens the effect of epistemic value on the activity of electronic word of mouth of tourists.